ANALISIS PENERAPAN PEMBELAJARAN BERDIFERENSIASI DALAM KURIKULUM MERDEKA DI SMAN 7 PADANG - Hikmah, Sri Hikmah Putri; Abna Hidayati; Rayendra; Mutiara Felicita Amsal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The study aims to analyze the application of differentiated learning consisting of content differentiation, process differentiation, product differentiation, and learning environment differentiation carried out at SMAN 7 Padang. The method used is Mixed Method with the Concurrent Embedded Strategy model. This model uses quantitative methods and qualitative methods. In this model, there are those who act as quantitative data, namely subject teachers of grade XI phase F of SMAN 7 Padang and students of phase F with a sample size of 15 teachers and 56 students and qualitative data using the Miles and Huberman Model. The results of the study showed that the application of differentiated learning carried out at SMAN 7 Padang on content differentiation was in the "Very Good" category with an average percentage of teachers of 82.50% and students of 81.25%, process differentiation was in the "Good" category with an average percentage of teachers of 80.93% and students of 76.64%, product differentiation was in the "Good" category with an average percentage of teachers of 86.67% and students of 80.63%. and the differentiation of the learning environment is in the "Good" category with an average percentage of teachers of 82.78% and students of 78.13%. Based on these results, it is concluded that overall the implementation of differentiated learning has been going well. However, obstacles were encountered including limited facilities in several classes and there were still teachers who were in the stage of understanding and learning the concept of differentiated learning.